2007
DOI: 10.1634/theoncologist.12-3-291
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Cannabis Does Not Influence the Clinical Pharmacokinetics of Irinotecan and Docetaxel

Abstract: Objective. To date, data regarding the potential of cannabinoids to modulate cytochrome P450 isozyme 3A (CYP3A) activity are contradictory. Recently, a standardized medicinal cannabis product was introduced in The Netherlands. We anticipated an increased use of medicinal cannabis concurrent with anticancer drugs, and undertook a drug-interaction study to evaluate the effect of concomitant medicinal cannabis on the pharmacokinetics of irinotecan and docetaxel, both subject to CYP3A-mediated biotransformation.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…Two studies in Table 3 did not meet inclusion criteria, but are included as they may provide additional insight into the specific pharmacokinetic effects described above. (Chetty et al, 1994;Engels et al, 2007) In a population pharmacokinetic analysis, self-reported regular cannabis use was associated with a 50% increase in estimated chlorpromazine clearance. (Chetty et al, 1994) This may reflect net CYP1A2 induction by non-THC components of smoked marijuana, consistent with results seen with theophylline.…”
Section: Data Not Meeting Inclusion Criteriamentioning
confidence: 99%
“…Two studies in Table 3 did not meet inclusion criteria, but are included as they may provide additional insight into the specific pharmacokinetic effects described above. (Chetty et al, 1994;Engels et al, 2007) In a population pharmacokinetic analysis, self-reported regular cannabis use was associated with a 50% increase in estimated chlorpromazine clearance. (Chetty et al, 1994) This may reflect net CYP1A2 induction by non-THC components of smoked marijuana, consistent with results seen with theophylline.…”
Section: Data Not Meeting Inclusion Criteriamentioning
confidence: 99%
“…However, smoked cannabis decreased the 8‐h area under the plasma concentration–time curve (AUC) of both nelfinavir (−17.4%, P = 0.46) and indinavir (−14.5%, P = 0.07). In a study involving 24 patients with cancer, cannabis administered as a medicinal tea did not alter the pharmacokinetics of the chemotherapy agents irinotecan and docetaxel 18 …”
mentioning
confidence: 96%
“…In a study involving 24 patients with cancer, cannabis administered as a medicinal tea did not alter the pharmacokinetics of the chemotherapy agents irinotecan and docetaxel. 18 articles Inhalation of vaporized cannabis delivers levels of THC and other cannabinoids similar to those from smoked marijuana but without exposure to combustion products. 19 Here we describe the disposition kinetics of sustained-release morphine and oxycodone, as well as pain ratings and other subjective responses, before and after 4 days of treatment with vaporized cannabis.…”
mentioning
confidence: 99%
“…Besides regular drugs for the management of nausea and vomiting, cannabis was demonstrated to be effective and was approved by the FDA [58]. No effects on docetaxel PK were demonstrated [59].…”
Section: Interactions With Supportive Medicationmentioning
confidence: 99%